Soybean Growth Performances Based on Biochar and Organic Liquid Fertilizer Optimization Application - Sumihar Hutapea, Rahmad Syah, Ismail Husein, Benny Gunarso, Gusmeizal (International Journal of Advanced Science and Technology, 2020)
This study aims to determine the effect of soybean growth based on biochar and organic liquid   fertilizer (OLF) application. The design used was random block factorial which consists B0 = without biochar, B1 = 5 tons biochar/ ha, B2 = 10 tons biochar / ha, combined with P0 = without OLF P1 = OLF concentration 1%, P2 = OLF concentration 2%, P3 = OLF concentration traction 3%. The results of this study indicate that biochar has high significant effect on plant height and leaf area. The best treatment is giving as much as 5 tons of biochar/ha. Liquid organic fertilization has high significant effect on plant height, and significantly affects the number of leaves, leaf area, and number of branches. The best treatment of OLF at a concentration of 1%. The best treatment of combination these organic wastes was of biochar 5 tons/ha and POC at 1% concentration.